1991
DOI: 10.1099/0022-1317-72-5-1051
|View full text |Cite
|
Sign up to set email alerts
|

Use of synthetic peptides to locate neutralizing antigenic domains on the fusion protein of respiratory syncytial virus

Abstract: Chemical and enzymic cleavages of the F~ subunit of the fusion (F) protein of respiratory syncytial (RS) virus showed that the sequence 184-Gly to 314-Trp reacted with neutralizing monoclonal antibodies (MAbs). Twelve synthetic peptides covering a part of this sequence were analysed for their immunoreactivity with neutralizing MAbs and anti-RS virus rabbit serum. Two sequential antigenic domains corresponding to amino acids 200 to 225 and 255 to 278 were defined with anti-RS virus rabbit serum. The peptides 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Strikingly, only the largest peptide (F215-275) induced an anti-peptide response in mice, but their sera reacted poorly with the virus and the animals were not protected against an RS virus challenge. This finding parallels the limited success of other authors in inducing anti-F antibodies using synthetic peptides with sequences included in antigenic area II (Bourgeois et al, 1991;Trudel et at., 1991). Thus, the induction of a protective humoral immune response with peptides remains a major obstacle to the design of an RS virus synthetic vaccine.…”
Section: Discussionsupporting
confidence: 67%
“…Strikingly, only the largest peptide (F215-275) induced an anti-peptide response in mice, but their sera reacted poorly with the virus and the animals were not protected against an RS virus challenge. This finding parallels the limited success of other authors in inducing anti-F antibodies using synthetic peptides with sequences included in antigenic area II (Bourgeois et al, 1991;Trudel et at., 1991). Thus, the induction of a protective humoral immune response with peptides remains a major obstacle to the design of an RS virus synthetic vaccine.…”
Section: Discussionsupporting
confidence: 67%
“…The two neutralizing, fusion-inhibiting MAbs chosen for mapping, 1E3 and RS348, have previously been shown to bind to the F protein in the presence of SDS and 2-mercaptoethanol indicating that at least some of their binding capacity is conformation-independent (Samson et al, 1986;Bourgeois et al, 1991). Both of these also bound to the C-terminal half of the molecule and to fragments containing amino acids 253 to 289 but not to fragments containing only sequences N-terminal to amino acid 212.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse ascitic fluids containing MAbs IE3 and 348 to the RS virus F protein were described previously (Samson et al, 1986;Bourgeois et al, 1991). Ascites fluid containing MAb 1G9 to the capsid protein of feline calicivirus which served as a control for non-specific binding was described by Carter et al (1989).…”
Section: Methodsmentioning
confidence: 99%
“…Bourgeois et al (1991) have reported the reactivity of one (RS-348) of nine MAbs with peptide 200 to 225 and Martin-Gallardo et al (1991) have reported that peptides spanning residues 289 to 298 react with MAb L4. However, no data from mutants escaping neutralization by MAbs RS-348 and L4 has been published to confirm the epitope location deduced using the peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have located a few epitopes on the primary structure of the F protein by (i) using synthetic peptides to examine the binding of MAbs (Trudel et al, 1987;Bourgeois et al, 1991;Martin-Gallardo et al, 1991) or polyclonal antibodies (Scopes et al, 1990), or (ii) isolating viruses that escape neutralization by anti-F protein MAbs in order to identify amino acid residues essential for epitope integrity . Since both approaches have limitations (see Discussion), we have used the two complementary strategies to locate the epitopes recognized by several anti-F protein neutralizing MAbs on the primary structure of the protein.…”
Section: Introductionmentioning
confidence: 99%